Recurrent respiratory diseases in practice of family physician and pediatrician: main issues (a literature review) - Lemko, O. I.; Lukashchuk, S. V (Zaporozhye Medical Journal, 2019)
The aim of the study – to analyze the professional literature and evaluate modern scientific trends concerning definition, peculiarities of etiopathogenesis, differential diagnosis and prevention of recurrent respiratory diseases (RRD) in the practice of family doctors and pediatricians. Conclusions. Respiratory diseases in children can play an ambiguous role, because on the one hand, they are an inducement for the host defenses, while they can cause secondary immune dysfunction in a significant increase in their incidence and severity, on the other. However, there are no specific criteria for RRD diagnosis. Contributing factors include harmful ecological conditions, unfavorable family history, absence of breastfeeding, presence of comorbid pathology and many other factors. Some children with RRD have immune dysfunctions, including changes in nonspecific protection and cellular immunity. Even if there are no changes in the main immunological indices, RRD can occur. Children with RRD require special attention, because severe, sometimes incurable diseases can be under the mask of frequent RRD. For such children family doctor and pediatrician should conduct a differential diagnosis with atopy, primary immune deficiency, gastroesophageal reflux, bronchial foreign body, cystic fibrosis, psychogenic cough and other diseases. Children with chronic infection should also be separated. In order to adequately assess the situation and develop a well-grounded treatment tactics for such patients, it is necessary to work out domestic criteria for assigning children to the RRD group. A physician should provide an individual approach to such a patient with optimal diagnostic methods and the development of management tactics both in acute episodes of respiratory diseases and during non-acute periods with the maximum involvement of drug-free modalities and for prevention of the pathological process progression.